Diferenças no rendimento desportivo entre os judocas séniores e juniores melhores classificados no ranking mundial - Sousa, J.; Lima, R.; Silva, R.; Camões, M.; Clemente, F. M. (Journal of Sport Pedagogy and Research, 2020)
The purpose of this study was to compare the match performance between the best ranked senior and junior Judo athletes. Twenty men athletes were analyzed (senior: N= 10; age: 27.7 ± 2.8 years junior: N=10; age: 19.3 ± 0.6 years). The twenty-four most recent matches per athlete were analyzed. The most recent matches were considered in a balanced way. Number of winnings and loses, Ippons, Waza-ari and penalties were coded. Moreover, gap between the athlete and the opponents were used as covariable for the comparisons. One-way ANCOVA revealed that junior athletes scored less Waza-ari than senior (-25.8%; p = 0.027; d = 0.182). Conclusions reveals that main performance is similar between junior and senior, with exception to the number of Waza-ari that is significantly larger in senior.